Autoimmune hepatitis in 847 childhoodonset systemic lupus erythematosus population: A multicentric cohort study - Balbi, Verena A. (2018)
Objective: To evaluate autoimmune hepatitis (AIH) in a multicenter cohort of childhood-onset systemic lupus erythematosus (cSLE) patients. Methods: This retrospective multicenter study included 847 patients with cSLE, performed in 10 Pediatric Rheumatology services of São Paulo state, Brazil. AIH was defined according to the International Autoimmune Hepatitis Group criteria (IAHGC). The statistical analysis was performed using the Bonferroni's correction (p < 0.0033). Results: AIH in cSLE patients confirmed by biopsy was observed in 7/847 (0.8%) and all were diagnosed during adolescence. The majority occurred before or at cSLE diagnosis [5/7 (71%)]. Antinuclear antibodies were a universal finding, 43% had concomitantly anti-smooth muscle antibodies and all were seronegative for anti-liver kidney microsomal antibodies. All patients with follow-up ≥18 months (4/7) had complete response to therapy according to IAHGC. None had severe hepatic manifestations such as hepatic failure, portal hypertension and cirrhosis at presentation or follow-up. Further comparison of 7 cSLE patients with AIH and 28 without this complication with same disease duration [0 (0-8.5) vs. 0.12 (0-8.5) years, p = 0.06] revealed that the frequency of hepatomegaly was significantly higher in cSLE patients in the former group (71% vs. 11%, p = 0.003) with a similar median SLEDAI-2 K score [6 (0-26) vs. 7 (0-41), p = 0.755]. No differences were evidenced regarding constitutional involvement, splenomegaly, serositis, musculoskeletal, neuropsychiatric and renal involvements, and treatments in cSLE patients with and without AIH (p > 0.0033). Conclusions: Overlap of AIH and cSLE was rarely observed in this large multicenter study and hepatomegaly was the distinctive clinical feature of these patients. AIH occurred during adolescence, mainly at the first years of lupus and it was associated with mild liver manifestations.